2000
DOI: 10.1159/000054278
|View full text |Cite
|
Sign up to set email alerts
|

Specific Serotonin Reuptake Inhibitor-Induced Decreases in Lymphocyte Activity Require Endogenous Serotonin Release

Abstract: Objectives: We have previously reported that acute administration of the specific serotonin reuptake inhibitor (SSRI), fluoxetine, resulted in a decrease in mitogen-induced blood lymphocyte proliferation. The present studies further examine the specificity of this response to serotonin reuptake systems and the potential role of endogenous serotonin in mediating these effects. Methods: Male Sprague-Dawley rats were treated intraperitoneally with the SSRIs, fluoxetine (6–10 mg/kg) or sertraline (20 mg/kg), dopam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 49 publications
0
27
0
2
Order By: Relevance
“…However, others found that in rats, elevations in extracellular 5-HT following reuptake inhibition by fluoxetine played an essential role in decreasing mitogen-induced lymphocyte proliferation [43]. …”
Section: Discussionmentioning
confidence: 99%
“…However, others found that in rats, elevations in extracellular 5-HT following reuptake inhibition by fluoxetine played an essential role in decreasing mitogen-induced lymphocyte proliferation [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Further support was given by the effect of 5-HT reuptake inhibitors, which decreased cell proliferation. Moreover, endogenous 5-HT release is required for observing decrease in lymphocyte activity by 5-HT reuptake blockers [55].…”
Section: Discussionmentioning
confidence: 99%
“…Acute treatment with SSRIs decreases lymphocyte proliferation. It has been proposed that such effect results from elevations in extracellular 5-HT due to inhibition of its uptake as a consequence of such treatment [28].…”
Section: -Ht Transportermentioning
confidence: 99%